9514 1404 393
Answer:
55. a[1] = 2; a[n] = 4·a[n-1]
56. a[1] = 48; a[n] = (1/2)·a[n-1]
57. a[1] = 36; a[n] = (1/3)·a[n-1]
Explanation:
A recursive rule comes in two parts: (1) the initial value; (2) the relation between a given value and the previous one.
For a geometric sequence, the form is pretty simple. The initial value is the first term. The present value is the last one multiplied by the common ratio.
a[1] = a_1
a[n] = r·a[n-1]
__
55. The common ratio is 8/2 = 4. The first term is 2. The recursive rule is ...
a[1] = 2; a[n] = 4·a[n-1]
__
56. The common ratio is 24/48 = 1/2. The first term is 48. The recursive rule is ...
a[1] = 48; a[n] = (1/2)·a[n-1]
__
57. The common ratio is 12/36 = 1/3. The first term is 36. The recursive rule is ...
a[1] = 36; a[n] = (1/3)·a[n-1]